Migração recente nas mesorregiões de Minas Gerais segundo os censos demográficos de 1991 e 2000 - Helder dos Anjos Augusto (2007)
The dynamic of space distribution of Minas Gerais population has supplied elements of great importance for discussion over configuration processes on new areas of population attraction. On this matter, the aim of this theses is based upon demographic census from 1991 to 2000 to analyse the recent immigration behavior on meso regions of Minas Gerais complemented by respective selected micro regions, baring in mind the origin and destination of such immigrants in Minas Gerais. Information concerning census data migrationmeans fixed date migration. For methodological effects of this study, it was used, for operation and collection of migration components, a few basics variable, such as state residence five years before census was held, once it distinguishes inter state immigrants, and meso region/micro region residents in Minas Gerais five years before census was held, which allows us to identify such immigrants within the state. Both collection and operation were performed by using SPSS software. The analyses developed on this study showed a relative knowledge of selected meso regions in Minas Gerais. The changes in migration in the mineirointer state status can be divided into two aspects of great importance: relative immigration rising and significant immigrant retraction. These opposed migrational components reveal in themselves on behavioral aspects that meso regions have presented in Minas Gerais other than other states and/or regions. The results of inter state migration indicate a different historical behavior of exodus. Among the twelve meso regionsin the state, 58,3% obtained a positive migrational inter state result between 1995/2000, against 33,3%, between 1986/1991.This migrational scenario shows strength of attraction e settling of population that some other meso regions have shown in five years` time, and it is the object of this study. An inter state setting, another important migration factor. The results point out to new directions and destinations of migrational flows in the State of Minas Gerais. Owing to the lack of life expectancy in some other states of the country, the strategy of migration has been tackled in destination/flows of short distances. Although this study does not intend to be the final word on such important phenomenon, it tries to track through desegregated analyses the main populational flows by means of its origin and/or destination, different states and among meso regions in the state of Minas Gerais. We can see that some meso regions in Minas, owing to its emerging economy, have been receiving a rising number of new immigrants, not only from inter state, but intra state too. Such meso regions have been gaining development which have made it possible for new economic activities, which, at the same time, have attracted new immigrants and kept settled down former residents.